Dakota Crumb : tiny treasure hunter - Michalak, Jamie; Murphy, Kelly (2021)
"Courageous little mouse Dakota Crumb ... scours the museum at night for rare artifacts, which she shares with her friends in the morning"--
2.2
Keywords: Mice -- Juvenile fiction; Museums -- Juvenile fiction; Friendship -- Juvenile fiction; Collectors and collecting -- Juvenile fiction; Picture books for children; Fantasy